MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN SOAL PENILAIAN AKHIR SEMESTER (PAS) MELALUI WORKSHOP DI MADRASAH BINAAN MIN 2 SIMALUNGUN - Enni Sunaga (Universitas Islam Negeri Sumatera Utara Medan, 2020)
This research is a School Action Research (PTS) which aims to improve the ability of teachers in making Final Semester Assessment (PAS) questions through a workshop at MIN 2 Simalungun. This research was carried out in 2 cycles, each cycle consisting of four stages, namely: Planning, Implementation, Observation, Reflection. The research subjects were the subjects in this study totaling 22 PAI teachers assisted at MIN 2 Simalungun. The data obtained are quantitative and qualitative data. The data were collected using the PAS Question Assessment observation sheet, interviews, and documentation, then the data were analyzed using data reduction and percentages. Based on the results of the research and discussion that have been described previously, it can be concluded that the workshop is suitable to be used to improve the ability of teachers to make PAS questions at MIN 2 Simalungun. This can be seen from the average percentage increase of 61% in cycle I to 82% in cycle II. With the appearance of each teacher at random, it can increase the teacher's motivation in completing the making of PAS questions.